Application of Mill Chatter Component Extraction and Root Cause Diagnosis in the Industrial Cold Rolling Mill - Xing Lu; Jie Sun; Qiyou Cheng; Dianhua Zhang (Shock and Vibration)
The third-octave mode mill chatter is a prominent rejection in the efficiency and quality of the strip. The third-octave mode chatter frequency is in the range of 150–250 Hz. Frequency analysis of vibration acceleration signal or original rolling process parameters is an effective method to detect third-octave mode chatter characteristics, and cold rolling mill chatter identification by frequency analysis is quite desired. However, original industrial data are contaminated by noise, making it difficult to obtain the principal component of 150–250 Hz when chatter occurs. Besides, it is necessary to find out the root rolling condition parameter causing chatter. To meet the early warning of the third-octave mode chatter in the production line, a new adaptive cuckoo search algorithm variational mode decomposition (CSA-VMD) and transfer entropy–based root cause diagnosis models are proposed. The verification results showed that the CSA-VMD method can extract the third-octave mode chatter component and avoid the mode mixing problem and endpoint effect. Early mill chatter warning should be provided when the tension fluctuation exceeds 20% in the uniform speed rolling phase.